Genome-wide identification and expression profiling reveal the regulatory role of U-box E3 ubiquitin ligase genes in strawberry fruit ripening and abiotic stresses resistance - Jiang, Leiyu; Lin, Yuanxiu; Wang, Liangxin; Peng, Yuting; Yang, Min; Jiang, Yuyan; Hou, Guoyan; Liu, Xiaoyang; Li, Mengyao; Zhang, Yunting; Zhang, Yong; Chen, Qing; et al. (Frontiers in Plant Science, 2023)
The plant U-box (PUB) proteins are a type of E3 ubiquitin ligases well known for their functions in response to various stresses. They are also related to fruit development and ripening. However, PUB members possess such roles that remain unclear in strawberry. In this study, 155 PUB genes were identified in octoploid strawberry and classified into four groups. Their promoters possessed a variety of cis-acting elements, most of which are associated with abiotic stresses, followed by phytohormones response and development. Protein-protein interaction analysis suggested that FaU-box members could interact with each other as well as other proteins involved in hormone signaling and stress resistance. Transcriptome-based and RT-qPCR expression analysis revealed the potential involvement of FaU-box genes in resistance to stresses and fruit ripening. Of these, FaU-box98 and FaU-box136 were positively while FaU-box52 was negatively related to strawberry ripening. FaU-box98 comprehensively participated in resistance of ABA, cold, and salt, while FaU-box83 and FaU-box136 were broadly associated with drought and salt stresses. FaU-box18 and FaU-box52 were ABA-specific; FaU-box3 was specific to salt stress. In addition, the functional analysis of a randomly selected FaU-box (FaU-box127) showed that the transient overexpression of FaU-box127 promoted the ripening of strawberry fruit, along with significant changes in the expression levels of some ripening-related genes and the content of organic acid and soluble sugar. Overall, these findings provided comprehensive information about the FaU-box gene family and identified the potential FaU-box members participating in stress resistance and strawberry fruit ripening regulation.